1976
DOI: 10.1021/bi00665a029
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence depolarization studies of phase transitions and fluidity in phospholipid bilayers. 1. Single component phosphatidylcholine liposomes

Abstract: The fluorescence depolarization associated with the hydrophobic fluorescent probe 1,6-diphenyl-1,3,5-hexatriene is used to monitor the changes in fluidity accompanying the gel-liquid crystalline phase transition in synthetic phosphatidycholine dispersions. The parameters of the phase transition are determined for both large, multilamellar liposomes and small, single-lamellar vesicles. These parameters are compared with those obtained using other techniques. In addition, the data are interpreted in terms of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
232
2
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(265 citation statements)
references
References 18 publications
30
232
2
1
Order By: Relevance
“…Furthermore, these studies show that the average environment of NBD-PE, as monito by the absolute position remains unaffected by these changes. These results are not particularly surprising in view of the fact that changes in membrane organization brought about by phase transition (or temperature) are largely restricted to the fatty acyl region of the membrane (Lentz et al, 1976) and are not sensed by the NBD moiety, which is linked to the headgroup in the case of NBD-PE and is located at the membrape interface (Chattopadhyay & London, 1987Paejano & Martin, 1988;Chattopadhyay, 1990;Mitra & Hammes, 1990;Wolf et al, 1992). It has been previously reported that the rates of solvent relaxation for probes that are not qeeply buried in the hydrocarbon interior of the membrane are more or less independent of temperature (Lakowicz et al, 1983a;takowicz & Keating-Nakamoto, 1984).…”
Section: 'Vv Crlvhmentioning
confidence: 94%
“…Furthermore, these studies show that the average environment of NBD-PE, as monito by the absolute position remains unaffected by these changes. These results are not particularly surprising in view of the fact that changes in membrane organization brought about by phase transition (or temperature) are largely restricted to the fatty acyl region of the membrane (Lentz et al, 1976) and are not sensed by the NBD moiety, which is linked to the headgroup in the case of NBD-PE and is located at the membrape interface (Chattopadhyay & London, 1987Paejano & Martin, 1988;Chattopadhyay, 1990;Mitra & Hammes, 1990;Wolf et al, 1992). It has been previously reported that the rates of solvent relaxation for probes that are not qeeply buried in the hydrocarbon interior of the membrane are more or less independent of temperature (Lakowicz et al, 1983a;takowicz & Keating-Nakamoto, 1984).…”
Section: 'Vv Crlvhmentioning
confidence: 94%
“…Structural Studies-Phospholipid acyl chain and head group packing order was determined by labeling rHDL with 1,6-diphenyl-1,3,5-hexatriene (DPH) and 1-(4-trimethylammoniumphenyl)-6-phenyl-1,3,5-hexatriene p-toluenesulfonate (TMA-DPH) (32,33), respectively. Steady state fluorescence polarization of the DPH-and TMA-DPHlabeled rHDL was measured at 5°C intervals from 5 to 50°C using an excitation wavelength of 366 nm.…”
mentioning
confidence: 99%
“…Thus, the kinetics of transport processes are more complex due to multiple diffusion barriers and it is not easy to obtain a uniform-sized population of vesicles. These disadvantages are overcome by the use of small, unilamellar vesicles; however, the surface of these vesicles has a high degree of curvature which affects many of the physical properties of the phospholipid in the vesicles (8,9). One would then expect the large, unilamellar vesicles to resemble most closely biological membranes.…”
mentioning
confidence: 99%